Assessment of Cousinia mindshelkensis populations (Asteraceae) at the Karatau Ridge, South Kazakhstan - AKERKE KENESBAY; ALFIYA KURMANTAYEVA; GULNARA SITPAYEVA; ALEXANDER SHMAKOV; ANASTASIA KOLTUNOVA; KANAT KULYMBET (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kenesbay A, Kurmantayeva A, Sitpayeva G, Shmakov A, Koltunova A, Kulymbet K. 2025. Assessment of Cousinia mindshelkensis populations (Asteraceae) at the Karatau Ridge, South Kazakhstan. Biodiversitas 26: 6174-6187. Cousinia mindshelkensis is a narrow-localized endemic species, spread by small populations in the central part of the Karatau ridge, Western Tien Shan, and is included in the Kazakhstan Red Book. This study aimed to assess the current state of C. mindshelkensis populations in the Karatau range based on morphological, ecological, and molecular characters. Four populations (P1-P4) were investigated. Morphological data was analyzed based on test plots with 10-15 individuals from each population, while ecological analysis included habitat description. Molecular data based on iPBS and ITS markers were carried out using the STRUCTURE program, cluster and phylogenetic analysis. Morphological traits showed high variability. Plants from P1 and P2 were the smallest, P4 was characterized by intensive vegetative growth with reduced flowering, whereas P3 demonstrated the best reproductive performance. The highest density occurred in P1 and P2 of 4.1±0.9 and 1.6±0.79 individuals/m², respectively. Ecological analysis indicated that the species inhabits petrophytic, mixed-herbaceous-woody-shrubby, and herbaceous-shrubby communities. Genetic diversity assessed by 3 iPBS markers was an average of 61.2% with the highest presented by iPBS2373 of 87.5% polymorphism and phylogenetic analysis confirmed all samples belong to a single clade. These results highlight the necessity of continuous monitoring and justify the inclusion of C. mindshelkensis among priority targets for biodiversity conservation in the region.